Evaluation of Recent Methods to Improve Recombinant Helicobacter Pylori Protein Yield and Solubility in Escherichia Coli Expression System - Huyen, Nguyen Thi; Phuong, Trinh Le; Trung, Do Thi Thanh; Diep, Le Hong; Yen, Pham Bao (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Successful expression of target genes, often indicated by high yield and solubility, is critical for studies involving recombinant proteins. Yet the most common bacterial expression system utilizing  Escherichia coli  as host cells is usually reported to produce low amounts of soluble target proteins. In this study, two  Helicobacter pylori   ( Hp )   genes, Hp lipase and Hp peptide deformylase ( Hp -PDF), whose encoded proteins are crucial for bacterial growth and colonization, thus could be used to screen potential anti- Hp  drugs, were designed to be expressed in such system. Genetic engineering, experimental biology, and computational biology methods were employed to enhance recombinant protein production. The result showed that Hp -lipase expression was most improved through construct design that used two restriction enzymes, Nde I and Xho I, including TEV sequence and 6xHis tag at the 3’ end of the target gene. Hp -PDF production increased significantly (24%) by optimizing culture condition and IPTG concentration according to Design Expert prediction together with cobalt supplementation. Either the addition of chemicals (glycylglycine) or heat shock method enhanced the yield and solubility of the studied proteins. Conclusively, it is suggested that combination of genetic engineering and computational optimization was efficient for recombinant protein expression in  E. coli   in addition to the conventional experimental biology methods. Keywords: Helicobacter pylori , lipase, peptide deformylase, Escherichia coli  expression system.